Kosovo Russia Serbia - Nyemann, Dorthe Bach (Politica, 2023)
Kosovo is neither the object nor the target of Russian influence operations. The purpose of delegitimizing Kosovo is to enhance and solidify the alliance between Russia and Serbia and the Serbian minorities across the Balkan region. Russian influence operations support the Serbian political elite by using Russian diplomatic levers and connections. Other Russian influence operations target the public, specifically influential Serbian groups in the right-wing opposition, in the military, and not least through the Orthodox Church throughout the Balkan region. The result is a high level of support for Russia among the Serbian population. This makes it extremely difficult for the Serbian government to make agreements with the EU or NATO and entraps Serbia in an alliance with Russia.